PENGARUH COUNTRY OF ORIGIN DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ACER - Putra, Heri Septiadi; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Purchase decisions can be influenced by various factors, including country of origin and perceived quality. This study aims to determine the influence of country of origin and perceived quality on the purchase decision of Acer laptops at the Muhammadiyah University of Bengkulu Students both partially and simultaneously. This study uses a quantitative research method with data collection techniques through questionnaires filled out by 75 respondents and analyzed using multiple linear analysis techniques.The results of the study showed that  the country of origin and perceived quality had a positive and significant influence partially or simultaneously on the purchase decision of Acer laptops with a t-value (2,922) < a table t-value (1,666) and a t-sig value (0.005) > α (0.05) on the county of origin variable, on  the perceived quality t-value variable ( 3,352 ) > the value of the t table (1.666) and the value of t sig (0.001) < α (0.05) with the value of f value of the Fcalculate value of 65,348 > F of the table (3.13) and the significance value of F sig (0.000) < α (0.05). This means that consumers consider the country of origin of the product and the perceived quality of the product before making a purchase decision. This research can contribute to the development of marketing strategies and product promotion on acer laptops The influence of country of origin and perceived quality on the purchase decision of acer laptops at the Muhammadiyah University of Bengkulu Students by 0.645 or 64.5% Key Words : Country Of Origin, Perceived Quality, Keputusan Pembelian